(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Nigeria is among the countries where human right abuses are recorded daily. This study assesses the United Nations and human rights protection in West Africa with focus on the Nigerian experience, 2015-2020. The study averred that human rights protection is guaranteed by the constitution but the reverse is the case in Nigeria with several cases of unlawful violation of civil, political and moral rights of Nigerians. The study argued that there is a significant nexus between human rights and democracy. The study argued that human rights have been violated in Nigeria. The paper adopted the Locke’s natural rights theory to ascertain the contributions of the United Nations in guaranteeing respect and protection of human rights in Nigeria. Source of data is secondary and the methods of data analysis are descriptive and content analytic models. The paper concluded that human rights protection is the major determinant of the practicability and success of democracy in any given society and should therefore be respected and safeguarded by the constitutions of every democratic society. The paper recommended, among others, that the Nigerian government through the National Assembly to establish a Local Human Rights Mechanism in all the 774 Local Governments like the local ombudspersons, anti-discrimination agencies, etc. The protection of human rights requires independent human rights mechanisms. In order for them to effectively discharge their functions, they should be provided with sufficient human and financial resources and be accessible to everyone within the respective locality. This would ensure human rights protection in the country.